2005
DOI: 10.1021/ol0508173
|View full text |Cite
|
Sign up to set email alerts
|

Practical Synthesis of (Z)-Polyaromatic and Heteroaromatic Vinylacetylenes

Abstract: [reaction: seet text] Two synthetic routes to several (Z)-polyaromatic and heteroaromatic substituted vinylacetylenes are described. The nature of aryl- or heteroaryl-substituted carboxaldehyde used as starting material dictated the choice of Wittig salt employed. A very attractive way to construct polyaromatic and pyridine-containing enynes is the reaction of polyaromatic and pyridine-containing aldehydes with bromomethyltriphenylphosphonium bromide in the presence of potassium tert-butoxide followed by a Son… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…Remarkably, compound 1b, recently prepared by a different protocol, 22 was obtained with our direct procedure in higher yield and stereoselectivity.…”
mentioning
confidence: 84%
“…Remarkably, compound 1b, recently prepared by a different protocol, 22 was obtained with our direct procedure in higher yield and stereoselectivity.…”
mentioning
confidence: 84%
“…Solution state UV–visible spectra were measured with a Shimadzu UV-3600 spectrophotometer, and fluorescence spectra were measured using a Edison RF-5301PC spectrofluoremeter. Starting materials 2i , 2j , 2k , 2z , and 2za were synthesized following literature protocols.…”
Section: Methodsmentioning
confidence: 99%
“…Prepared according to a procedure reported by Jianbo, Wang, and co-workers, the mixture of ( E : Z = 1:1); yellow liquid (yield: 337.9 mg, 63%); 1 H NMR (400 MHz, CDCl 3 ) δ 7.47–7.40 (m, 4H), 7.38–7.33 (m, 7H), 7.24 (dd, J = 5.1, 1.2 Hz, 1H), 7.13 (dd, J = 3.7, 1.2 Hz, 1H), 7.05 (dd, J = 5.1, 3.7 Hz, 1H), 6.93 (dd, J = 5.1, 3.7 Hz, 1H), 6.87 (s, 1H), 6.73 (dd, J = 3.6, 1.1 Hz, 1H), 6.49 (s, 1H); 13 C NMR (101 MHz, CDCl 3 ) δ 143.9, 141.4, 140.8, 140.4, 140.2, 138.6, 130.4, 129.4, 128.7, 128.5, 128.5, 128.4, 128.3, 128.1, 128.5, 127.5, 127.2, 126.6, 126.5, 125.6, 104.3; HRMS (ESI) m / z : calcd for C 12 H 10 BrS [M + H] + : 264.9681; found: 264.9685.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a variety of methods for their synthesis have emerged, there is still significant need for more direct methods to afford functionalized indolizine derivatives. During their work on the practical synthesis of ( Z )-heteroaromatic vinylacetylenes, Hayford et al serendipitously found the formation of indolizines upon desilylation of ( Z )-2-pyridine-silylated vinylacetylene with cesium or potassium fluoride and different alcohols as solvents or cosolvents (Figure ) . A mechanistic pathway involving a Michael-type addition to the vinylacetylene and subsequent six-electron electrocyclic ring closure to afford the indolizine was proposed (Figure ).…”
mentioning
confidence: 99%